Peningkatan kemampuan mengidentifikasi unsur intrinsik cerita fiksi melalui penerapan model pembelajaran cooperative integrated reading and composition (CIRC) pada peserta didik kelas IV sekolah dasar - Anggita Tiara Dewi; Rukayah Rukayah; Tri Budiharto (Universitas Sebelas Maret, 2020)
Abstract. The purpose of this reseacrh is to describe the process of application learning model of Cooperative Integrated Reading and Composition (CIRC) that can improve the ability to identify intrinsic elements of fiction stories for students grade IV at State Elementary School Tunggulsari II No.179 Laweyan, Surakarta in the academic year 2019/2020. This research was divided in two cycles. The subjects of this reseacrh were teacher and 30 students grade IV. Data collected techniques through observation, interviews, document analysis, and tests. Data validity through content validity, technical triangulation, and source triangulation. Quantitative data were analyzed using descriptive comparative techniques and qualitative data were analyzed using interactive models. This result of this research is increasing the ability to identify the intrinsic elements of fiction stories from pre-action that gets classical completeness by 13.33%, increasing in cycle I to 30%, and ending in cycle II becomes 83.33%. The conclusions in this study indicate an increase in the ability to identify intrinsic elements of fiction stories for students grade IV at State Elementary School Tunggulsari II No.179 after the implementation learning model of Cooperative Integrated Reading and Composition (CIRC). Keywords: CIRC, intrinsic element of fiction stories, elementary school